VALIDITAS DAN RELIABILTAS ANGKET MINAT BELAJAR - Ilham Dhin; Asep Samsudin; Wiwin Yuliani (IKIP Siliwangi, 2023)
Interest in learning is the most important thing for the learning success process of students, to stimulate students to achieve the expected learning achievements, interest in learning will determine the success of students in learning. Seeing the importance of interest in learning, relevant media such as questionnaires are needed as a means of measuring the tendency of students to interest in learning and tested for validity and reliability. The subjects of this study were students of SMA Darul Falah Batujajar class XI totaling 10 students. the results of the validity test of the 26 question points there are 14 valid points and the reliability with a value of 0.743 the value is quite large. Thus, interest in learning can be used to measure the learning achievement of students.Keywords : Learning Interest, Validity,Reliability,